Penggunaan Router Mikrotik Untuk Memberikan Kualitas Suara Yang Dihasilkan Pada Protokol IPV4 Dan IPV6 - Habibie, Ananda; Diansyah, Tengku Mohd; Handoko, Divi (Journal of Computer Science and Informatics Engineering, 2024)
IP addresses are also known as computer identification codes on the network / internet, every computer connected to the network must have an IP address on each interface and the IP address itself must be unique because no computer can use the same IP address. same. 32-bit IPv4 addresses will be increasingly limited and difficult to obtain in the future, therefore a new development of IP addresses is needed, namely, Internet Protocol vesion 6 (IPv6) or known as Internet Protocol Next Generation (IPNG) is a layer third protocol created to replace IPv4. At this time not only computers are connected to the internet, but everyday equipment such as cell phones, PDAs, household appliances and so on are also connected to the internet. The author tries to do a comparative study of the use of IPv4 and IPv6 in building a Local Area Network (LAN). This research is expected to help users who will make the transition from IPv4 to IPv6